2018
DOI: 10.18632/oncotarget.25993
|View full text |Cite
|
Sign up to set email alerts
|

Combination of resveratrol and 5-flurouracil enhanced anti-telomerase activity and apoptosis by inhibiting STAT3 and Akt signaling pathways in human colorectal cancer cells

Abstract: Colorectal cancer is one of the leading causes for mortalities worldwide. The most common cause of colorectal cancer mortality is hepatic metastasis. There has been a limited advancement in the targeted-therapies for metastatic colorectal cancer. Conventional chemotherapeutic agent 5-fluorouracil has been used for various cancer treatments including colorectal cancer. Development of drug resistance and severe toxicity are major hurdles for its use in clinical setting. Resveratrol is a natural polyphenolic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 52 publications
0
46
0
Order By: Relevance
“…Inhibition of STAT3 signaling plays a critical role in RES-induced suppression of several cancer types. RES inhibits STAT3 Tyr705 phosphorylation in ovarian cancer, 20,21 pancreatic cancer, 22 head and neck tumor, 23 osteosarcoma, 24 colorectal cancer, 25 colon cancer, [22][23][24][25][26] and STAT3 S727 phosphorylation in head and neck tumor and colorectal cancer. 23,25 Similarly, STAT3 signaling is a critical target of RES to induce apoptosis of SiHa and HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of STAT3 signaling plays a critical role in RES-induced suppression of several cancer types. RES inhibits STAT3 Tyr705 phosphorylation in ovarian cancer, 20,21 pancreatic cancer, 22 head and neck tumor, 23 osteosarcoma, 24 colorectal cancer, 25 colon cancer, [22][23][24][25][26] and STAT3 S727 phosphorylation in head and neck tumor and colorectal cancer. 23,25 Similarly, STAT3 signaling is a critical target of RES to induce apoptosis of SiHa and HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that resveratrol inhibits IL-6induced transcriptional activity of STAT3 in human prostate cancer LNCaP-FGC cells (18), and STAT3 axis in primary glioblastoma tumor initiating cells (19). Inhibition of STAT3 signaling plays a critical role in resveratrol-induced suppression of several types of cancer, including ovarian cancer (20,21), pancreatic cancer cells (22), head and neck tumor cells (23), osteosarcoma (24), colorectal cancer (25), colon cancer (26). In these types of cancers, it has been shown that resveratrol inhibits STAT3 Tyr705 phosphorylation (22)(23)(24)(25)(26) and STAT3 S727 phosphorylation (23,25).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of STAT3 signaling plays a critical role in resveratrol-induced suppression of several types of cancer, including ovarian cancer (20,21), pancreatic cancer cells (22), head and neck tumor cells (23), osteosarcoma (24), colorectal cancer (25), colon cancer (26). In these types of cancers, it has been shown that resveratrol inhibits STAT3 Tyr705 phosphorylation (22)(23)(24)(25)(26) and STAT3 S727 phosphorylation (23,25). Zhang et al showed that STAT3 signaling is more critical for cervical cancer cells and is the major target of resveratrol because selective inhibition of STAT3 rather than Wnt or Notch activation commits SiHa and Hela cells to apoptosis (27).…”
Section: Introductionmentioning
confidence: 99%
“…Research on apoptosis and autophagy caused by phytochemicals seems to be mostly polarized on certain types of cancer, i.e., breast, prostate and colon cancer and more frequently involving curcumin, flavonoids, and resveratrol [ 116 ]. Curcumin and resveratrol also induce apoptosis via the same survival pathways targeted by several flavonoids, e.g., PI3K/Akt [ 117 , 118 ], MAPK/JAK2/STAT3 [ 119 , 120 ], p38MAPK/ERK1/2/JNK [ 121 , 122 ], Wnt/β-catenin [ 123 , 124 ], NF-κB [ 125 , 126 ]. Besides these major pathways, phytochemicals are able to induce apoptosis in cancer cells, targeting many further signaling and biochemical mechanisms.…”
Section: Insights On the Role Of Flavonoids In Cancermentioning
confidence: 99%